(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article deals with the concept of a paradigm and issues of language research within the framework of the modern linguistic paradigm, provides various systems of priority paradigms in linguistics, and explores the modern cognitive -discursive paradigmof linguistic knowledge.